Comparative evaluation of natural tupping with fixed-time laparoscopic and cervical insemination techniques using chilled semen in estrous synchronized sheep - MALIK, A A; FAZIL, M R; KHATUN, A; ATHAR, H; KHAN, H M; SHAH, R A (The Indian Journal of Animal Sciences, 2023)
The present study was conducted in crossbred ewes to compare the efficiency of different artificial insemination techniques with natural tupping following fixed time artificial insemination using fresh semen. Crossbred ewes (n=29) were randomly divided into three groups with 10 animals in natural tupping (NT) and laparoscopic artificial insemination (LAI) groups and nine animals in cervical artificial insemination (CAI) group. Ewes in all the treatment groups were subjected to the same estrus induction protocol: insertion of intravaginal progesterone sponges for 10 days followed by an intramuscular injection of 500 IU eCG at the time of sponge withdrawal. Immediately after removal of sponges, animals of NT group were kept with proven breeding rams up to 72 h. Fixed time cervical or laparoscopic insemination was done at 48 h after sponge removal. The insemination was repeated 12 h later in CAI group. The pregnancy and lambing rates were significantly higher in NT group (90%, 90%), than CAI group (55.5%, 55.5%) and LAI group (20%, 10%). The prolificacy rate was significantly higher in CAI group (180%) than NT group (111.1%) and LAI group (100%). The serum progesterone concentration was higher in pregnant ewes on day 10, day 17 and day 35 than non-pregnant ewes. The fixed time cervical insemination following intravaginal progesterone sponges for 10 day+eCG protocol resulted in better pregnancy rate and prolificacy rate in crossbred ewes during breeding season.